Battles lost and won great campaigns of World War II - Baldwin, Hanson Weightman, 1903-1991. (New York, Harper & Row, 1966)
An evaluation of eleven crucial campaigns and battles of World War II.
"We want war!" : the beginning, the Polish campaign, September 1-October 6, 1939 -- The Battle of Britain, July-September, 1940 -- Crete : the winged invasion, May 20-31, 1941 -- "The Rock" : the fall of Corregidor, December, 1941-May 6, 1942 -- Stalingrad : point of no return, June 28-1942-February 2, 1943 -- The Sicilian campaing : strategic compromise, July 10-August 17, 1943 -- Tarawa : a study in courage, November 20-23, 1943 -- Normandy : the beginning of the end, June 6, 1944 -- The greatest sea fight : Leyte Gulf, October 23-26, 1944 -- The Battle of the Bulge : a case history in intelligence, December, 1944-January, 1945 -- The greatest sea-air battle in history : Okinawa, April 1-June 22, 1945.
"Notes, bibliographies, and acknowledgements": pages 385-508
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: 1939-1945; World War, 1939-1945 -- Campaigns